The relationship between the dietary index based Meiji nutritional profiling system for adults and lifestyle-related diseases: a predictive validity study from the National Institute for Longevity Sciences—Longitudinal Study of Aging - Yu, Tao; Zhang, Shu; Wakayama, Ryota; Horimoto, Tomohito; Tange, Chikako; Nishita, Yukiko; Otsuka, Rei (Frontiers in Nutrition, 2024)
Background: Nutritional profiling system (NPS) hold promise as public health tools aiming at assisting individuals in making healthier food choices. The Meiji NPS for adults specifically targets lifestyle-related diseases prevalent among Japan's adult population, including overweight/obesity, hypertension, diabetes, and dyslipidaemia. This study examined the cross-sectional association between the Meiji NPS for adults Dietary Index (MNfA-DI) and indicators of lifestyle-related diseases in a population. Methods: The study comprised 1272 middle-aged individuals (40-64 years, 50.1% male) who participated in the seventh wave (2010-2012) of the National Institute for Longevity Sciences -Longitudinal Study of Aging project, with no missing data on three-day dietary records. The MNfA-DI was computed at the individual diet level (accounting for the whole diet) using arithmetic energy-weighted means. A higher MNfA-DI indicated a greater nutritional quality of an individual's overall diet. Lifestyle-related disease indicators included body mass index (BMI,kg/m 2 ), body fat (%), systolic and diastolic blood pressure (mmHg), fasting plasma glucose (mg/dL), HbA1c (%), triglyceride levels (mg/dL), LDL, and HDL cholesterol levels (mg/dL). A multiple regression model was used to assess the association between the MNfA-DI and lifestyle-related disease indicators, adjusting for demographics, socioeconomic status, lifestyle factors, disease history, and energy intake as covariates, depending on the outcome. Results: The median (interquartile range) age and MNfA-DI were 53.0 (46.0, 59.0) years and 10.1 (6.0, 14.0) points, respectively. MNfA-DI was negatively associated with body fat (partial regression coefficient (95% confidence interval) -0.04 (-0.07, -0.01)), diastolic blood pressure (-0.08 (-0.17, -0.002)), fasting plasma glucose (-0.18 (-0.33, -0.01)), and triglyceride (-1.36 (-2.16, -0.55)). Additionally, MNfA-DI was also associated with almost indicators (except for LDL and HDL cholesterol) among participants with a BMI between 18.5 and 24.9 kg/m 2 . Conclusion: These findings suggest that the Meiji NPS for adults could be associated with a lower risk of lifestyle-related diseases. In addition, from a public health nutrition perspective, the Meiji NPS for adults may be useful to assess the food healthiness of the adult population.